(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article analyzes the evolution of accounting in Uzbekistan, starting with its formation in the Soviet period and ending with the transition to International Financial Reporting Standards (IFRS). The key stages of development, including the implementation of the National Accounting Standards (NAS), as well as the problems and prospects of integration with IFRS are considered. effectiveness of financial reporting. The article also discusses the main challenges faced by enterprises and forecasts for the development of the accounting system in Uzbekistan.